2015
DOI: 10.1007/s11156-015-0534-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraday jumps and trading volume: a nonlinear Tobit specification

Abstract: This paper investigates the relationship between trading volume and volatility for four international stock markets (US: S&P500, UK: FTSE100, France: CAC40 and Germany: DAX30) in a context of global financial crisis. Unlike previous related studies, we use intraday data and apply a nonlinear econometric model to assess this relationship. In particular, we first break down intraday realized volatility into its continuous and jump components using the non-parametric approach developed by Barndorff-Nielsen and Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Recently, to look deeper into the volume-volatility nexus, a stream of research decomposes return volatility into a continuous component, which is private information-driven, and jumps component, which is public information-driven. For example, Jawadi et al (2015) use intraday data from four major stock markets, namely, Frankfurt, London, New York and Paris. The results point to a significantly positive association between volume and volatility components (jumps and continuous part), suggesting a strong link between trading volume and both public and private information.…”
Section: Return Volatility-volume Relationshipmentioning
confidence: 99%
“…Recently, to look deeper into the volume-volatility nexus, a stream of research decomposes return volatility into a continuous component, which is private information-driven, and jumps component, which is public information-driven. For example, Jawadi et al (2015) use intraday data from four major stock markets, namely, Frankfurt, London, New York and Paris. The results point to a significantly positive association between volume and volatility components (jumps and continuous part), suggesting a strong link between trading volume and both public and private information.…”
Section: Return Volatility-volume Relationshipmentioning
confidence: 99%
“…Kallsen et al [19] considered jumps, stochastic fluctuations and leverage effects in the application of the BN-S model, and gave option pricing according to the quadratic change of the stock price process. Jawadi et al [18] used the BN-S model to decompose the intra-day volatility into continuous volatility and jumping volatility, and studied the relationship between the trading volume and volatility of different international stock markets. Habtemicael [13] innovatively proposed an optimized BN-S model of superimposed Lévy processes driven by τ (ν, α) and inverse Gaussian distribution, and modeled to realize the exchange of variance and volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Before their studies, Chow et al (Chow, Hung, Liu, & Shiu, 2013) also investigated the manipulation cases on Taiwan markets and found that expiration day effect partially contributes to the market close manipulation attempts. Based on the study, Huang et al (Huang & Cheng, 2014) studied the new closing mechanism on the market variables and the aggressiveness of the trading activity while Jawadi et al (Jawadi, Louhichi, Cheffou, & Randrianarivony, 2016) further studied the trading volumes and volatility across four international markets.…”
Section: Introductionmentioning
confidence: 99%